Isolated Right Atrial Enhancement with Atrial Standstill: An Uncommon Presentation of Emery–Dreifuss Muscular Dystrophy - Basavaraj Biradar; Jineesh Valakkada; Anoop Ayyappan; Ajay Alex (Indian Journal of Radiology and Imaging)
Emery–Dreifuss muscular dystrophy (EDMD) is a rare inherited syndrome that affects muscles, joints, and the heart. The classic clinical triad includes early joint contractures, slowly progressive muscle weakness, and cardiac abnormalities. The common cardiac manifestations include conduction disturbances, systolic dysfunction, and dilated cardiomyopathy and may be associated with left ventricular noncompaction with an increased risk of thromboembolic events. Conduction disturbances include atrial arrhythmias, atrial standstill, complete heart block, or ventricular tachyarrhythmia. Cardiac magnetic resonance imaging (CMR) can help in the diagnosis of this condition by identifying chamber dilatation, systolic dysfunction, and late gadolinium enhancement of the atrium. Additional MRI finding of paraspinal muscle atrophy, an important finding in this muscular dystrophy, helped in reaching a confident imaging diagnosis. Our case in this article highlights the clinical and CMR findings of this rare condition.